PERBANDINGAN EFEK PEMBERIAN ANESTESI XYLAZIN-KETAMIN HIDROKLORIDA DENGAN ANESTESI TILETAMIN-ZOLAZEPAM TERHADAP CAPILLARY REFILL TIME (CRT) DAN WARNA SELAPUT LENDIR PADA ANJING - Gorda, I Wayan; Wardita, A.A. Gde Jaya; Dharmayudha, A.A. Gde Oka (Buletin Veteriner Udayana, 2012)
This study is to determine the effect of xylazine-ketamine hydrochloride combined withtiletamin-zolazepam combination to Capillary Refill Time (CRT), paleneus of mucousmembranes, heart pulse frequency and pulse before anesthesion, when anesthezed andduring anesthetion. The experimental was carried duct on local dog. The experimental design has 2 treatments : dose I (2 mg/kg body weight of xylazinehydrochloride ; 15 mg/kg body weight of ketamine hydrochloride) and dose II (20 mg/kgbody weight of zoletil). Each of treatment use 5 local dogs and total of 10 dogs for all of thetreatments. Data were analyzed by analysis of varience test and the score data analyzed byfriedman test. A results showed the combination of xylazine-ketamine hydrochloride andtiletamin-zolazepam combination could increase to Capillary Refill Time (CRT) andmucous membranes colour.
Keywords: xylazine; ketamine; tiletamine; zolazepam; CRT